Biocompatible reinforcement of poly(Lactic acid) with graphene nanoplatelets - Carolina Gonçalves (2018)
A recently made available form of graphene nanoplatelets (GNP-C) is investigated for the first time as reinforcement filler for PLA. GNP-C, with thickness of about 2 nm and length 1-2 m, was incorporated at different loadings (0.1-0.5 wt%) in poly(lactic acid) (PLA) by melt blending. The effect of varying mixing time and mixing intensity was studied and the best conditions were identified, corresponding to mixing for 20 min at 50 rpm and 180 degrees C. Thermal analysis (differential scanning calorimetry and thermogravimetric analysis) indicated no relevant differences between pristine PLA and the composites. However, the rate of thermal degradation increased with loading, due to the dominant effect of heat transfer enhancement over mass transfer hindrance. Raman spectroscopy allowed confirming that increasing graphene loading or decreasing mixing time translates into higher nanoplatelet agglomeration, in agreement with the observed mechanical performance and scanning electron microscopy imaging of the composites. The composites exhibited maximum mechanical performance at a loading of 0.25wt%: 20% increase in tensile strength, 12% increase in Young's modulus, and 16% increase in toughness. The incorporation of 0.25wt% GNP-C did not affect human fibroblasts (HFF-1) metabolic activity or morphology. POLYM. COMPOS., 39:E308-E320, 2018. (c) 2016 Society of Plastics Engineers